2017
DOI: 10.18520/cs/v112/i05/1003-1011
|View full text |Cite
|
Sign up to set email alerts
|

Scientometric Profile of Global Rice Research during 1985-2014

Abstract: A bibliometric analysis is conducted to study the history and status of rice research from 1985 to 2014. We find that the number of publications has grown rapidly over the past 30 years, especially in Asia. However, the gap of research output quality between Asian countries/regions and USA is obvious. The keywords co-occurrence analysis shows that the genetic analysis for agronomic traits is a hot topic. It could be expected that more technologies such as metabonomics and proteomics will be integrated to accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Temporal trend of studies with microcrustaceans Our results showed that there was an increase in the number of studies with microcrustaceans over 35 years in the rice fields; however, the number of studies was low compared to a previous scientometric study involving a general analysis of rice fields (Liu et al 2017). This reduced number of studies may be due to the use of a specific group in our study in contrast to the general analysis of the other studies (Morooka et al 2014, Liu et al 2017).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Temporal trend of studies with microcrustaceans Our results showed that there was an increase in the number of studies with microcrustaceans over 35 years in the rice fields; however, the number of studies was low compared to a previous scientometric study involving a general analysis of rice fields (Liu et al 2017). This reduced number of studies may be due to the use of a specific group in our study in contrast to the general analysis of the other studies (Morooka et al 2014, Liu et al 2017).…”
Section: Discussionmentioning
confidence: 48%
“…Temporal trend of studies with microcrustaceans Our results showed that there was an increase in the number of studies with microcrustaceans over 35 years in the rice fields; however, the number of studies was low compared to a previous scientometric study involving a general analysis of rice fields (Liu et al 2017). This reduced number of studies may be due to the use of a specific group in our study in contrast to the general analysis of the other studies (Morooka et al 2014, Liu et al 2017). Moreover, it may be related to less incentive for ecological research on these groups in rice fields, since general scientific research involving rice has grown by about 6.9% per year (Liu et al (2022) 94(4) e20201752 8 | 16 from ours to compile and filter the studies to be analyzed.…”
Section: Discussionmentioning
confidence: 48%
“…Some major rice‐producing countries (e.g., China, Japan, United States, and the Philippines) contributed most of publications in Rice (Cañas‐Guerrero et al., 2013). Liu, Zhang, and Wang (2017) also indicated that China, Japan, and the United States were the most productive countries regarding rice research. The International Rice Research Institute in the Philippines ranked first in research institutions with the most publications and total citations.…”
Section: Resultsmentioning
confidence: 99%
“…The study is conducted to elucidate the pattern of collaboration operating in the field of rice crop research and aims to achieve the following objectives: (1) to explore the growth characteristics of knowledge productions for India in the field of rice crop research during 1995-2014; (2) to identify the type of co-authorship pattern and measures the strength of collaboration among Indian rice scientists; (3) to construct the domestic and international collaboration profile of Indian rice scientists; and (4) to examine the pattern of collaboration taking place between major agencies active in rice crop research in India. Although bibliometric methods have already received enough attention in the rice crop research, the majority of previous studies [7,8] harbors on traditional methods such as co-author and co-citation analysis, which do not provide a complete picture of collaboration practiced in rice crop research. An attempt is made in the study to apply both co-author and social network analysis to capture broadly the intricacies of collaboration operating in the field of rice crop research in India.…”
Section: Objectives Of the Studymentioning
confidence: 99%